Relationship between peri-coronary inflammation and coronary vascular function in patients with suspected coronary artery disease - Chen, Mengyu; Liu, Bing; Li, Xu; Li, Dong; Fan, Lijuan (Frontiers in Cardiovascular Medicine, 2024)
Background In this study, we aim to investigate the relationship between the attenuation of peri-coronary adipose tissue (PCAT) in patients with suspected coronary artery disease (CAD) and the assessment of coronary vascular functions using coronary flow reserve (CFR). Methods We included 364 patients who underwent 13N-NH3 positron emission tomography/computed tomography and coronary computed tomography angiography (CCTA). We determined the relationship between fat attenuation index (FAI), PCAT volume, and other qualitative CT-derived anatomic parameters with CFR. Results We detected a decrease in CFR (<2.5) in 206 (57%) patients. At the patient level, those with reduced CFR showed a significantly higher prevalence of diffused atherosclerosis (41% vs. 23%; P < 0.001) and higher FAI (−75.5 HU vs. −77.1 HU; P = 0.014). In patients without obstructive CAD, FAI was significantly higher in those with reduced CFR (−75.5 HU vs. −77.7 HU, P = 0.026). On the vessel level, 1,092 vessels were analyzed, and 642 (59%) exhibited reduced CFR. The vessels with reduced CFR presented a significantly higher prevalence of obstructive CAD (37% vs. 26%; P < 0.001), diffused atherosclerosis (22% vs. 11%; P < 0.001), low-attenuation plaque (6% vs. 3%; P = 0.030), and positive remodeling (7% vs. 2%; P = 0.001). FAI was higher in vessels with reduced CFR (−80.8 HU vs. −81.8 HU; P = 0.045) than in normal CFR. In the patient-level analysis, obstructive CAD, diffused atherosclerosis, and FAI were independently linked with CFR. FAI was still associated with global CFR after adjusting for traditional risk factors (age, hypertension, diabetes, hyperlipidemia, and smoking). FAI remained independently associated with reduced CFR in patients without obstructive CAD. Conclusions Coronary perivascular inflammation evaluated by CCTA was independently associated with coronary vascular function. In patients without obstructive CAD, FAI was higher in the presence of reduced CFR. Altogether, FAI can help reveal microcirculatory damage in patients who do not exhibit epicardial artery stenosis.